Formas larvais de Trematoda provenientes de gastrópodes límnicos da microrregião Rio de Janeiro, sudeste do Brasil (Lundiana: International Journal of Biodiversity, 2002)
The study of freshwater molluscs associated with helminth larval stages from the state of Rio de Janeiro revealed different morphological types of cercariae. Among them, Pleurolophocercus cercaria, Echinostomocercaria, Strigeocercaria, and Xiphidiocercaria, were found in Biomphalaria tenagophila (Orbigny, 1835), Physa marmorata Guilding, 1828 and Melanoides tuberculatus (Müller, 1774). For the later species is the first occurrence as an intermediate host for tremadodes in Brazil and the first record of Pleurolophocercus cercaria in Brazil.